Respuesta :

y+1=3(x+1)
if you need to simplify to slope intercept form then y=3x+2

[tex]\bf (\stackrel{x_1}{-1}~,~\stackrel{y_1}{-1})\qquad (\stackrel{x_2}{1}~,~\stackrel{y_2}{5}) \\\\\\ slope = m\implies \cfrac{\stackrel{rise}{ y_2- y_1}}{\stackrel{run}{ x_2- x_1}}\implies \cfrac{5-(-1)}{1-(-1)}\implies \cfrac{5+1}{1+1}\cfrac{6}{2}\implies 3 \\\\\\ \begin{array}{|c|ll} \cline{1-1} \textit{point-slope form}\\ \cline{1-1} \\ y-y_1=m(x-x_1) \\\\ \cline{1-1} \end{array}\implies y-(-1)=3[x-(-1)]\implies y+1=3(x+1)[/tex]

ACCESS MORE